Gene Cloning and Gene Expression Characteristics of Alcohol Dehydrogenase in Osmanthus fragrans var. semperflorens - Zhang, Dangquan (Emirates Journal of Food and Agriculture, 2018)
Because of a lot of aroma components in the flowers, Osmanthus fragrans is widely used as ornamental tree species and its flowers is used as materials of spices and food additives. Alcohol dehydrogenase (ADH) plays an important regulation role in growth, development, stress resistance and aroma synthesis of plants. Using the flowers of O fragrans var. semperflorens as materials, the full-length cDNA of ADH gene (termed OfADH) was successfully cloned through rapid amplification of cDNA ends (RACE), which has the 1128 bp open reading frame (ORF) in length and codes 375 amino acids. The results of conserved domain analysis show that the OfADH belongs to the zinc-dependent medium-chain dehydrogenase /reductase (MDR) superfamily, contains 22 NAD(P) binding sites in the liver_alcohol_DH_like conserved domains, and also has the PLN02740 (Alcohol dehydrogenase-like) domain. The results of semi-quantitative RT-PCR indicate that the expression level of OfADH in O. fragrans flowers is consistent with the rule of aroma formation and release, while the expression of OfADH in leaves is positively correlated with high temperature stress, suggesting that OfADH has obvious functional diversity in regulation of aroma synthesis and response to high temperature stress.